CLINICAL AND IMMUNOBIOCHEMICAL MARKERS IN THE DIAGNOSIS OF BRONCHIAL ASTHMA COMBINED WITH TYPE 2 DIABETES MELLITUS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The aim of the study was to investigate clinical, laboratory and immunobiochemical markers in patients with bronchial asthma (BA) combined with type 2 diabetes mellitus (T2DM). A comparative analysis of clinical manifestations, carbohydrate metabolism parameters, fibrinolysis and the antioxidant system was performed.